A Study on Factors to Influence Consumer Behavior: Analyzing the Impact of Progression, Privatization, and Globalization on Consumer Behavior in the Beauty Care Products Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Progression, Privatization and Globalization Policy of India impacted numerous beauty care products organizations exchanging and fabricating in our nation. The accessibility of numerous brands in Karnataka gives different options in contrast to the customer. These makers offer comparable incentive, and give exceedingly tweaked products. Beautifying agents products execution isn't viewed as imperative for customers now, rather they search for those separating parameters. The primary goal of this paper is to recognize the conceivable parameters that impact the consumer purchasing standards of conduct of beauty care products in the State of Karnataka. It is additionally intended to build up a hypothetical model, which impact the consumer purchasing behaviors of beautifying agents products, so further research should be possible, in view of the model and the recognized parameters.